First report of Pantoea stewartii subsp. indologenes causing leaf blight on rice in Malaysia - Azizi, M. M. F.; Ismail, S. I.; Hata, E. M.; Zulperi, D.; M. Y., Ina Salwany; Abdullah, M. A. F. (American Phytopathological Society, 2019)
In November and December of 2017, leaf samples from rice (Oryza sativa) exhibiting leaf blight symptoms were collected from commercial fields in Kedah and Selangor, Malaysia, with about 80% disease incidence. Symptoms were water-soaked lesions from the upper part of the leaf blade, which later turned into brown stripes (Mondal et al. 2011), as typically caused by Xanthomonas oryzae pv. oryzae (Niño-Liu et al. 2006). Twenty strains of bacteria were isolated from the diseased samples from both fields, and eight isolates (MF1, MF2, MF3, MF4, MF5, MF7, MF8, and MF9) suspected to be Pantoea species were subjected to further characterization. Bacterial colonies were isolated from surface-sterilized infected leaf tissue using 75% ethanol and 1% sodium hypochlorite, rinsed three times in sterilized water, macerated in sterilized water, placed on King’s B agar medium, and incubated for 48 h at 28°C. Single colonies were transferred and maintained on nutrient broth medium. All isolated bacteria were gram-negative facultative anaerobes, motile, positive for catalase and gelatin tests, hydrolyzing starch, incapable of producing hydrosulfuric acid, indole positive, and able to produce acetoin. Colonies were round, smooth with irregular edges, and produced yellow pigment on King’s B agar medium. Polymerase chain reaction using specific primers targeting the gyrb gene of Pantoea genome was performed, and the ∼600-bp amplicons were sequenced (Kini et al. 2017). BLASTn analysis revealed all strains had 99% similarity to the Pantoea stewartii reference strain (ARC646) in the GenBank database (accession no. KX342016). These sequences were later deposited in GenBank (accession nos. MH300616 to MH300621 and MH673052 to MH673054). A phylogenetic tree constructed based on the concatenated nucleotide sequences of the gyrb gene showed that all strains were 99% similar to P. stewartii reference strains (accession nos. KX342015, KF554590, KT7295191, and KX342016). The strains were tested with subspecies-specific primers of P. stewartii subsp. stewartii and P. stewartii subsp. indologenes targeting housekeeping gene gaIE that encodes UDP-glucose 4-epimerase to confirm the subspecies (Gehring et al. 2014). Positive bands were produced by all strains from gaIE indologenes subspecies, each producing a ∼267-bp amplicon. All strains were identical to the reference strain of P. stewartii subsp. indologenes (NCPPB 1845) in GenBank database (accession no. HG792431). To test pathogenicity, 10 ml of 108 CFU/ml bacterial suspension of each strain was inoculated into 4-week-old rice seedlings of MR269 variety using the leaf clipping method (Kauffman et al. 1973), and they were kept in the greenhouse with temperature ranging from 26 to 35°C. All eight strains of P. stewartii subsp. indologenes produced symptoms similar to those originally found in the rice fields, including yellowish necrotic water-soaked lesions, which later turned to typical blight at 2 weeks postinoculation. Strains were reisolated from diseased leaves using the same method mentioned above and confirmed as P. stewartii subsp. indologenes by sequence analysis of the gaIE gene, thus fulfilling Koch’s postulates. To the best of our knowledge, this is the first report of leaf blight disease caused by P. stewartii subsp. indologenes on rice in Malaysia.